IMPROVEMENT OF SPEECH COMPETENCES IN THE SPEECH PROCESS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Speech activity develops throughout a person's life, in the family, society, and education. In the education of the native language, one of the pressing issues of contemporary science is the development of students' speech competencies and the skills to express their thoughts independently, freely, and substantiated".